Utility of MRI in diagnosis of empty Sella syndrome in a young female with amenorrhoea and bilateral nipple discharge - Suthar, Pokhraj P.; Parmar, Gaurav R.; Trivedi, Chinmay; Vithlani, Hemen I. (International Journal of Research in Medical Sciences, 2017)
Empty sella syndrome is a rare disease in which sella turcica appears empty. It can be asymptomatic or may have symptoms due to hormonal disturbances. Here we report a case of 35-years-old female who presented with amenorrhoea and bilateral nipple discharge.